Needs Satisfaction And Social Adjustment Among Secondary School Students In Of Cross River State, Nigeria - Amalu, Melvina N; Bekomson, Achi N; Enamhe, Dorn Claimz; Chukwurah, Margaret U; Amalu, Nneka Sophie (Universitas Negeri Makassar, 2024)
The study investigated the influence of needs satisfaction on social adjustment among students in Calabar Municipality, Cross River State, Nigeria. To achieve this purpose, three hypotheses were formulated to guide the study. The study adopted a survey research design. A stratified and purposive sampling technique was used to select a total of three hundred (300) students in study. The instrument used for data collection was questionnaire titled” Needs Satisfaction and Social Adjustment Scale (NSSAS). The questionnaire was validated by experts in measurement and Evaluation and the reliability established using Cronbach alpha reliability estimate were .81 and the coefficient was high for the instrument to be considered dependable and consistent. The test statistics used for the study was simple regression. This statistics was selected based on the nature of the hypotheses and how they were measured in the instrument. The result showed that there is significant influence of psychological, physiological and social needs satisfaction on social adjustment among students. Based on the finding, recommendations were made that students’ physiological needs such as food shelter and clothing should be made a priority by parents in order to help the learner adjust speedily to the demands of the environment.